On Becoming a Modern Architect: Eero Saarinen's Early Work 1928-1948 - Peter C. Papademetriou (Oz, 1987)
The debate in architectural theory and criticism of the past decade has centered around reintegration of a supposed lack of symbolic content in architectural form through, to a large part, a repudiation of its most recent legacy, the Modernist period and specifically the stylistic imperatives of its most obvious manifestation, the International Style.